The politics of modernism : against the new conformists - Williams, Raymond (Verso, 1989)
This is an exploration of the ambivalent relationship between revolutionary politics and modernist or avant-garde art. Williams clarifies many of the issues that have dogged recent critical discussion: the term "modernism" itself; the distinction between modernism and avant garde; and the possibility of a cultural theory "beyond the modern" which avoids the pitfalls of postmodernism. Raymond Williams is the author of "Politics and Letters", "Problems in Materialsm and Culture", "Resources of Hope" and "Writing in Society